Drought‐Triggered Magmatic Inflation, Crustal Strain, and Seismicity Near the Long Valley Caldera, Central Walker Lane. Issue 6 (21st June 2019) - Hammond, W. C.; Kreemer, C.; Zaliapin, I.; Blewitt, G.
Abstract: We use GPS data to show synchronization between the 2011 and 2016 drought cycle in California, accelerated uplift of the Sierra Nevada Mountains, and enhanced magmatic inflation of the Long Valley Caldera (LVC) magmatic system. The drought period coincided with faster uplift rate, changes in gravity seen in the Gravity Recovery and Climate Experiment (GRACE), and changes in standardized relative climate dryness index. These observations together suggest that the Sierra Nevada elevation is sensitive to changes in hydrological loading conditions, which subsequently influences the LVC magmatic system. We use robust imaging of horizontal GPS velocities to derive time‐variable shear and dilatational strain rates in a region with highly variable station distribution. The results show that the highest strain rates are near the eastern margin of the Sierra Nevada and western edge of the Central Walker Lane (CWL) passing directly through LVC. The drought period saw geographic shifts in the distribution in active shear strain in the CWL more than 60 km from the LVC, delineating the minimum extent over which the active magmatic system affects the CWL tectonic environment. We analyze declustered seismicity data to show that locations with higher seismicity rates tend to be (1) areas with higher strain rates and (2) areas in which strain rates increased during drought‐enhanced inflation. We hypothesize that drought conditions reduce vertical surface mass loading, which decreases pressure at depth in the LVC system, in turn enhances magmatic inflation, and drives horizontal elastic stress changes that redistribute active CWL strain and modulate seismicity. Plain Language Summary: We show that there were connections between the recent drought in California to changes in uplift rate of the Sierra Nevada, magmatic inflation at the Long Valley Caldera near Mammoth, CA, and earthquakes in the region. We use GPS, seismic, gravity, and climate data to show that the speed of uplift of the Sierra Nevada is sensitive to big changes in surface and groundwater (e.g., in snow, streams, lakes, and aquifers) and that these changes correlate with movements within the large volcano. A plausible explanation is that the weight of snow and water loads the surface and changes pressures deep in the Earth. As the Sierra Nevada was unloaded during recent drought, there was less pressure on the magmatic system, allowing fluids to rise or expand more easily. When that occurred, it provided an outward horizontal push on the crust, influencing small‐ to moderate‐sized earthquakes up to 60 km away. We show where and when these changes occurred and specific examples of earthquakes that may have been triggered by this inflation. Key Points: Faster Sierra Nevada uplift during the 2011–2016 drought in California coincided with faster magmatic inflation at the Long Valley Caldera Faster magmatic inflation changed the rate and distribution of crustal strain in the Central Walker Lane, >60 km from Long Valley Seismicity patterns in the Central Walker Lane suggest that long‐term crustal strain may be driven in part by Long Valley magmatic inflation